Phylogenetic position of Theileria cervi detected in Blastocerus dichotomus (Artiodactyla: Cervidae) with clinical symptoms from argentina - Sebastian, Patrick; Falzone, Martin; Lois, Maria F.; Sartori, Rodrigo; Zimmerman, Jennifer; Tarragona, Evelina Luisa; Nava, Santiago (Elsevier, 2022)
The results of this study document the molecular detection of Theileria cervi in a symptomatic adult marsh deer Blastocerus dichotomus (Artiodactyla: Cervidae) from Argentina and characterize the phylogenetic position of the Argentinian strain. The animal was founded with signs of obnubilation, anaemia, and ataxia on Isla Talavera in the Paraná Delta, Argentina. Biochemical, haematological and post mortem histopathological studies resulted in the detection of symptoms associated with Theileria infections. Piroplasmid DNA was detected in a blood sample and the complete 18S rDNA gene sequence could be archived. Phylogenetic analyses of the obtained sequence verify the genetic relationship of the Argentinian strain with strains of T. cervi found in other deer species in North America. This result, together with reports of T. cervi detected in various deer species that inhabit countries from Canada in the North to Argentina in the Western Hemisphere, indicates that this Piroplasmorida possess a low host specificity. Although the majority of T. cervi infections results asymptomatic or in mild course of the disease, it must be considered that T. cervi is circulating in Argentinian B. dichotomus populations and can cause serve course of the disease. Therefore, further studies are needed to investigate its prevalence, distribution and veterinary impact.